Analysis of non‐traumatic truncal back pain in patients who visited an emergency room. Issue 2 (28th January 2014) - Nagayama, Masataka; Yanagawa, Youichi; Aihara, Koichiro; Watanabe, Shin; Takemoto, Masaaki; Nakazato, Tomoko; Hashimoto, Takashi; Takayama, Toshio; Takazawa, Yuuji; Iba, Toshiaki; Kaneko, Kazuo; Tanaka, Hiroshi
<x xml:space="preserve">Abstract</x> Aim To investigate epidemiology of acute non‐traumatic back pain using modern diagnostic methods in patients who visited an emergency room. Methods The medical charts were retrospectively reviewed for all patients with back pain who were treated in our hospital. In addition, the patients were divided into two groups based on whether they were treated at the hospital or as outpatients. Results There were 95 patients with non‐traumatic acute back pain. Leading cause of back pain was ureterolithiasis (53 cases), followed by pyelonephritis (10), orthopedic disease including two cases of purulent spondylitis (24), aortic disease (3), pancreatitis (1), renal bleeding (1), adrenal bleeding (1), psoas abscess (1), and torsion of an ovarian tumor (1). All cases of pyelonephritis, aortic disease, purulent spondylitis, renal bleeding, adrenal bleeding, psoas abscess, and torsion of an ovarian tumor were treated in admission. Using a multiple logistic regression analysis, blood pressure, age, and body temperature were the only factors that were independently associated with whether the patient was admitted or treated as an outpatient. Conclusion This study showed that urological diseases are the most common cause of back pain in patients who visit the emergency room, followed by orthopedic disease. Older age, low blood pressure, and high body temperature were independently associated with the decision to admit the patient who might have lethal disease.